Economic and financial realities in Trinidad and Tobago (a mid-year report). - Farrell, Terrence W. (1992)
Presents developments in the last few years, as well as a broad outline of current economic and financial circumstances. Stresses the need for discerning and creating investment opportunities which would help overcome the current problems and raise standard of living.